PALLIATIVE CARE RECOVERY OUTCOMES: NATURE OF RECOVERY OUTCOMES AMONG CANCER PATIENTS IN NAIROBI AND NYERI COUNTIES, KENYA - Wang'ombe, Joyce; Kathungu, Beatrice (Journal of Health, Medicine and Nursing, 2021)
Purpose: This study sought to find out nature of recovery outcomes among cancer patients attending palliative care in Nairobi and Nyeri County Methodology: The study adopted a correlation research design. The target population were the cancer patients, attending treatment at the three palliative care units in Nairobi and Nyeri Counties. Systematic random sampling technique was used in the study to obtain a sample of 96 participants. Semi structured questionnaires were used to collect data. Data was analysed using both descriptive and inferential statistics, namely Pearson Moment Correlation Coefficient(r). Findings: Result showed that, majority of the respondents (65.5%) had a low level of recovery outcomes, while 32.1% had a high level of recovery outcomes. results indicate that the lowest score on recovery outcomes was 31, while the highest score was 74. The mean score was 47.0+9.465, which indicates that the recovery outcomes fell in the low range. These findings were not unusual considering that most of the patients were newly diagnosed with cancer and for some respondent's metastasis had set in. Conclusion: The study concluded that the two most significant challenges encountered in palliative care were, patient experiencing isolation and lacking finances. Provision of financial support and increasing the number of counselling sessions were suggested as possible strategies for enhancing patient recovery outcomes Recommendation: This study recommended that the palliative care units staff should encourage participation of family members, friends and significant others in the cancer continuum, so as to provide psychological and social support to patients Unique contribution to theory, practice and policy Patients under palliative care could adopt group psychotherapy, including cognitive-behavioural, informational, non-behavioral, social support, and using unusual treatments such as music and art therapy to curb cancer. More cancer related programs enhancing patients AQ should be put in place by the counsellors in order to increase the patients AQ in the palliative care units from moderate level to high level of AQ in order to boost recovery outcomes